Tests for occult blood - Craig, D. G. (1975)
Cancer of the large bowel is an important cause of morbidity and mortality. The barium enema is still the most reliable diagnostic tool, but the selection of the proper candidates for this moderately expensive and time-consuming examination presents a real problem. To wait for significant symptoms of change in bowel habits, such as unexplained anaemia, is hazardous. Testing for occult blood has fallen into disuse in most general practices. This paper discusses some of the available techniques for this procedure which I suggest offer a worthwhile aid to examination of patients with possible alimentary neoplasm.